Intentionality of Point of View in Narrative Discourse: A Pragmatic Approach in Saudi Novel Samples - Al-Shammari, Saud Bin Minahi Al-Rammahi (Arts for Linguistic & Literary Studies, 2023)
This study aims to reveal the purposes of narrative discourse underlying the narrative point of view in a sample of four Saudi novels: Mohammed Hassan Alwan’s A Small Death, Omaima Al-Khamis’s The Book Smuggler, Maqboul Mousa Al-Alawi’s Seferbirlik, and Awadh Shaher Al-Usaimi’s Almarkh Fire. The research consists of a preface, a theoretical introduction based on the concepts of intentionality and point of view and four sections, followed by a conclusion. The first section discusses the point of view of the narrator and the characters in A Small Death. The second section discusses the point of view of the narrator and the characters in The Book Smuggler. The third section is concerned with revealing it in Seferbirlik. The fourth section discusses it in Almarkh Fire. The research concluded that the four narrative models included rhetorical objectives that ranged between direct and indirect, which are partial objectives distributed among the folds of the discourse, and as a whole formed the comprehensive objectives of the narrative discourse depending on the context and had an effective role in attributing the point of view to the narrator and to some characters